Hypomagnesemia in hemodialysis patients taking proton pump inhibitors (Journal of Fatima Jinnah Medical University, 2020)
Background: Proton pump inhibitors (PPIs) are in routine widely prescribed to hemodialysis patients. Recent studies have reported the association of PPIs use with hypomagnesemia in patients with long term hemodialysis. This study aims to determine the frequency of hypomagnesemia in patients of hemodialysis taking proton pump inhibitors.Patients and methods: This cross-sectional study was conducted in the Department of Nephrology of Sandman Provincial Hospital Quetta from 01-6-2019 till 01-9-2019. A total of 120 patients (52 PPI users and 68 non-PPI users) who were on HD for more than 06 months were included. Data regarding age, gender, duration of hemodialysis and taking PPIs were collected. Determination of serum magnesium was made by taking 3 different samples at 2 weeks’ interval and the mean value of serum magnesium was calculated. Serum Mg2+ levels
Keywords: Hemodialysis; Proton pump inhibitors; Hypomagnesemia